Immunopathologic characterization of ultrasound-defined synovitis in rheumatoid arthritis patients in clinical remission. Issue 1 (December 2016) - Ramírez, Julio; Celis, Raquel; Usategui, Alicia; Ruiz-Esquide, Virginia; Faré, Regina; Cuervo, Andrea; Sanmartí, Raimon; Pablos, José; Cañete, Juan
Abstract Background Patients with rheumatoid arthritis (RA) in clinical remission may have ultrasound-defined synovitis according to the presence of power Doppler (PD) signal. The objective was to describe the immunopathologic characteristics of ultrasound-defined synovitis compared with synovitis in patients with clinically active RA. Methods We included between 6 and 8 ultrasound-guided synovial biopsies per patient from 20 patients with RA in clinical remission (DAS28-ESR <2.6) with PD signal, 22 synovial tissue samples (ST) from patients with clinically active RA (swollen joint with confirmed inflammatory synovial fluid) as inflammatory controls, and 10 ST from non-inflammatory controls. Immunostaining for CD3 (T lymphocytes), CD20 (B lymphocytes), CD68 (macrophages), CD117 (mast cells), hsp47 (fibroblasts), bFGF and CXCL12 (angiogenic factors) was made and quantified by digital image analysis. The number of CD31 vessels/mm2 was quantified. Results RA patients in remission with PD signal had significantly reduced synovial T-cell, B-cell, mast cell and fibroblast density, but similar macrophage infiltration compared with patients with clinically active RA. Vascularity, bFGF and CXCL12 were partially reduced in RA patients in remission with PD signal compared to those with active RA, but were significantly higher compared with ST from non-inflammatory controls. During the 12-month follow up, 8/20 RA patients (40 %) lost remission: all had synovial hypertrophy grade ≥2 and significantly more synovial B cells and mast cells than patients maintaining remission. Conclusions Asymptomatic ultrasound-defined synovitis and clinically active arthritis differ in the degree of infiltrating lymphoid, mast cells and fibroblast density, but are similar with respect to macrophage infiltration. Persistently increased angiogenic factor expression and vascularity may explain the persistence of a PD signal.